Web-page screenshots as an evidence in civil procedure of Ukraine - Голубєва, Неллі Юріївна; Голубєва, Н. Ю.; Голубева, Нелли Юрьевна; Holubieva, Nelli Yu.; Golubeva, Nelli; Дрогозюк, Крістіна Борисівна; Дрогозюк, К. Б.; Дрогозюк, Кристина Борисовна; Drohoziuk, Kristina B.; Drogoziuk, Kristina (Masaryk University, 2019)
Currently the question about the possibility of including a screenshot of a web-page to the base of evidence in civil procedure of Ukraine remains open. The problem is a lack of systematic rules for determining procedures for obtaining electronic evidence, in particular, screenshots, in Ukrainian legislation, as well as possibilities for their use while considering civil cases. Various electronic evidence should correspond various admissibility criterias, and therefore the admissibility of electronic evidence should be examined separately according to each type of evidence. Separate issues of investigation, fixation and certification of web-screenshots as evidence in civil procedure of Ukraine are considered in this article. The analysis of legal regulation and problems of the practical implementation of use of web-pages screenshots in Ukrainian civil procedure are carried out. The ways of implementation of recommendation rules for registration and fixation of web-screenshots in civil procedure, which can be applied for all European states, are proposed.

Наразі питання про можливість включення скріншоту веб-сторінки до доказової бази в цивільному процесі України залишається відкритим. Проблема полягає у відсутності в українському законодавстві системних правил визначення порядку отримання електронних доказів, зокрема скріншотів, а також можливостей їх використання при розгляді цивільних справ. Різні електронні докази повинні відповідати різним критеріям прийнятності, і тому прийнятність електронних доказів повинна розглядатися окремо відповідно до кожного виду доказів. У цій статті розглядаються окремі питання розслідування, фіксації та засвідчення веб-скріншотів як доказів у цивільному процесі України. Проведено аналіз правового регулювання та проблем практичної реалізації використання скріншотів веб-сторінок в українському цивільному процесі. Запропоновано шляхи впровадження рекомендаційних правил реєстрації та фіксації веб-скріншотів у цивільному процесі, які можуть застосовуватися для всіх європейських держав.
Golubeva N. Web-page screenshots as an evidence in civil procedure of Ukraine / N. Golubeva, K. Drogoziuk // Masaryk University Journal of Law and Technology. – Vol. 13 (1). - Masaryk University, 2019. - P. 87-113.
Keywords: civil procedure; civil procedure of Ukraine; electronic documents; electronic evidence; means of proof; proving; screenshots; website; цивільний процес; цивільний процес України; електронні документи; електронні докази; засоби доказування; доведення; скріншоти; веб-сайт; Research Subject Categories::LAW/JURISPRUDENCE::Procedural law::Civil procedure